Digital Era for Quality Education: Effectiveness of Discovery Learning with Android to Increase Scientific Literacy - Uswatun Karimah; Titin Sunarti; Munasir Munasir (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This study analyzes the effectiveness of discovery learning models integrated with Android. Method: The method used is the literature review method. A literature review is a type of research used to collect data and information from various references. This research analyzes 20 national and international articles that can be accounted for. The articles used are articles published in 2018-2023. The steps taken in this study are identifying topics, finding and selecting appropriate articles, analyzing and synthesizing literature, and concluding. Results: Based on the results of research and analysis, it can be supposed that (1) the application of the discovery learning model can improve students' scientific literacy; (2) The use of Android in learning can improve students' scientific literacy. Novelty: This research reveals that integrating discovery learning learning models with androids can improve students' scientific literacy. This discovery invites researchers, educators, and governments to develop and facilitate discovery learning integrated with Android.